Answer: see proof below
Step-by-step explanation:
Given: A + B + C = π → A + B = π - C
→ C = π - (A + B)
Use Sum to Product Identity: cos A + cos B = 2 cos [(A + B)/2] · cos [(A - B)/2]
Use Product to Sum Identity: 2 sin A · sin B = cos [(A + B)/2] - cos [(A - B)/2]
Use the Double Angle Identity: cos 2A = 1 - 2 sin² A
Use the Cofunction Identity: cos (π/2 - A) = sin A
Proof LHS → RHS:
LHS: cos A + cos B + cos C
= (cos A + cos B) + cos C
The proof for this is simple. Let's say that A + B + C = π. From here on we require several trigonometric identities that must be applied.
Hope that helps!
I think its 625, deeply sorry if it is not.
Answer:
$600
Step-by-step explanation:
Answer:
CANDY diabeatise sgdigduejsdid
Answer:
y int is -4. slope is negative. slope is rise/run. in the graph is rises 2 for every 3 it goes to the left. this means your slope is 2/3
put all that together
-2/3x -4 is your equation
Answer:
The solution of such a system is the ordered pair that is a solution to both equations. To solve a system of linear equations graphically we graph both equations in the same coordinate system. The solution to the system will be in the point where the two lines intersect.
Step-by-step explanation:
Answer:
The solution of such a system is the ordered pair that is a solution to both equations. To solve a system of linear equations graphically we graph both equations in the same coordinate system. The solution to the system will be in the point where the two lines intersect. please give brainiest
Step-by-step explanation: